FACTORS RELATED TO ABORTION INCIDENCE IN PREGNANT WOMEN AT BHAYANGKARA HOSPITAL, DEPOK, INDONESIA - Elfitriani, Bovi; Desmie, Noer (Proceedings of the International Conference on Applied Science and Health, 2017)
Introduction: WHO estimates that the incidence rate of abortion case worldwide is 15%. The incidence rate in developed countries such as USA is 10-20%, compared to developing nations such as Zimbabwe where it reaches 28%. In Southeast Asia, an estimate of 4.2 million abortions occur every year. In Indonesia, the national rate of abortion incidence reaches up to 18-19%, while West Java province reported that there are 400,000 cases each year. Bhayangkara Brimob Hospital Depok, situated in West Java, recorded 25.1% of abortion incidence rate in 2012. Objectives: To determine the maternal factors associated with the abortion incidence among pregnant women in Bhayangkara Brimob Hospital Depok. Method: This research used secondary data with descriptive research method and cross sectional by using random sampling technique. The total population is 340 people and the sample taken in this study amounted to 77 people with abortion cases. The analysis used is univariate and bivariate. Statistical test analysis through Chi Square test, with É = 0.05 and odds ratio. Results: The study revealed that there was a significant relationship between age (P value = 0.016, OR = 5,200), parity (P value = 0.044, OR = 4,167), occupation (P value = 0.009, OR = 5,750), anaemia (P value = 0.013, OR = 5,556), and no significant association with previous abortion history (P value = 0.942, OR = 0.781). Conclusion: Based on the study, the result of this research will support the information about the factors related to abortion incidence in pregnant women and can further be used as a guidance in abortion prevention.Â